Off-the-shelf human decellularized tissue-engineered heart valves in a non-human primate model - Weber, Benedikt; Dijkman, Petra E.; Scherman, Jacques; Sanders, Bart; Emmert, Maximilian Y.; Grünenfelder, Jürg; Verbeek, Renier; Bracher, Mona; Black, Melanie; Franz, Thomas; Kortsmit, Jeroen; Modregger, Peter; et al. (Biomaterials, 2013)
Heart valve tissue engineering based on decellularized xenogenic or allogenic starter matrices has shown promising first clinical results. However, the availability of healthy homologous donor valves is limited and xenogenic materials are associated with infectious and immunologic risks. To address such limitations, biodegradable synthetic materials have been successfully used for the creation of living autologous tissue-engineered heart valves (TEHVs) in vitro. Since these classical tissue engineering technologies necessitate substantial infrastructure and logistics, we recently introduced decellularized TEHVs (dTEHVs), based on biodegradable synthetic materials and vascular-derived cells, and successfully created a potential off-the-shelf starter matrix for guided tissue regeneration. Here, we investigate the host repopulation capacity of such dTEHVs in a non-human primate model with up to 8 weeks follow-up. After minimally invasive delivery into the orthotopic pulmonary position, dTEHVs revealed mobile and thin leaflets after 8 weeks of follow-up. Furthermore, mild-moderate valvular insufficiency and relative leaflet shortening were detected. However, in comparison to the decellularized human native heart valve control – representing currently used homografts – dTEHVs showed remarkable rapid cellular repopulation. Given this substantial in situ remodeling capacity, these results suggest that human cell-derived bioengineered decellularized materials represent a promising and clinically relevant starter matrix for heart valve tissue engineering. These biomaterials may ultimately overcome the limitations of currently used valve replacements by providing homologous, non-immunogenic, off-the-shelf replacement constructs.